Scoping Review: The Role of Micronutrients (Fe, Zn, Iodine, Retinol, Folate) During Pregnancy - Al Rahmad, Agus Hendra (Jurnal Kesehatan Manarang, 2023)
Pregnant women are highly vulnerable to nutritional problems such as Chronic Energy Deficiency (CHD), deficiency of micronutrient intake (iron, zinc, and vitamin A intake), anemia, and Iodine Deficiency Disorder (IDD). Micronutrient deficiencies in pregnant women must be specifically prevented. A healthy and nutritionally balanced diet is essential for maternal and fetal health. The review study aimed to identify the role of micronutrients (Fe, Zn, Iodine, Vitamin A, and Folate) during pregnancy. The literature review used a scoping review technique referring to the Arksey and O'Malley framework. The literature review (2012-2022) used the online databases PubMed, Science Direct, Willey Online Library, ProQuest, and Springer. The search used Medical Subject Headings (MeSH), including the variables "role of nutrients," "pregnant women," "micronutrients (Fe, Zn, Iodine, Vitamin A, Folate)," and "during pregnancy." The selection of articles using the PRISMA Flowchart starts with identification, screening, eligibility, and selected articles. Results, this literature study has found 18 articles that are feasible and meet the criteria. This study identified that women preparing for pregnancy and pregnant women must pay attention to nutrient intake at conception, nutritional status in trimesters I to III, and the role and intake of micronutrients during pregnancy both for maternal health and optimal health fetal growth. Obtaining adequate and balanced micronutrient intake is very important to maintain the health of pregnant women and fetuses during pregnancy. In conclusion, the role of micronutrients is significant for pregnant women and fetuses. One of the most important for pregnant women and fetuses is vitamin B9), which helps form red blood cells, maintain a healthy nervous system, and help in iron metabolism. Folic acid also helps in fetal growth and development, and iron helps produce red blood cells and maintains adequate oxygen levels in the body.